Kemandirian Energi Listrik di Pasar Seni Kuta dengan menggunakan Sistem PLTS - Wiranatha, I Dewa Gde Bayu; Hartati, Rukmi Sari; Setiawan, I Nyoman (Majalah Ilmiah Teknologi Elektro; Vol 23 No 1 (2024): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2024)
The Kuta Art Market, is a modern market that was recently revitalized in 2023. The building has renewable energy potential of PLTS on the roof area, when this potential can be exploited then the electricity consumption of the Kuta Art Market Building is no longer supplied by conventional power plants (PLN) but will enjoy clean energy of autonomous plants such as PLTS. The aim of this study is to identify the potential for generating electricity on the roof of the Kuta Art Market, determine the capacity of the battery as a reserve source of energy and the value of the investment. The research steps of this thesis calculate the solar energy potential in the area of the Kuta Art Market by using PVsyst software, collect the load profile of the Kuta Art Market. The next step is to compute the capacity of the PLTS - inverter then determine the battery capacity required according to the load profile of the Kuta Art Market and then determines the investment cost to build the solar power plant on the rooftop of the Kuta Art Market as well as to evaluate the potential cost savings that can be achieved by using solar energy as a primary resource. The total roof area of the Kuta Art Market is 780,455 m 2 with energy potential of 166,23 kW. Based on the design results, PLTS will be built with a capacity of 61,6 kWp, with total battery capacity 3200 Ah. Total investment of Rp. 1,162,938.563 is required for the construction of PLTS, a payback period of 15 years 8 months, NPV of Rp. 204,439.887,26 and IRR of 8,06%. Based on the values above, it indicates that the PLTS project on the roof of the Kuta Art Market building is feasible to carry out.